Expression of IL-17 on Breast Cancer Mice Treated by Combination of Phyllanthus Urinaria and Catharanthus roseus Extract - Shofiyah, Aya; M. Sasmito Djati; Muhaimin Rifa'i (The Journal of Experimental Life Science, 2022)
This study aimed to evaluate the effect of combination Phyllanthus urinaria and Catharanthus roseus in breast cancer mice based on the expression of IL-17. 7,12-Dimethylbenz(α)anthracene (DMBA) was injected intraperitoneally into normal mice at dose 1.5 mg.kg-1 weight to obtain breast cancer mice. Total of 24 experimental mice divided into normal mice (N), breast cancer mice (K), breast cancer mice with cisplatin (C) treatment (5 mg.kg-1 weight), breast cancer mice with combination extract Dose 1 (P. urinaria 500 mg.kg-1 weigt + C. roseus 15mg.kg-1 weight), breast cancer mice with combination extract Dose 2 (P. urinaria 1000 mg.kg-1 weight + C. roseus 75mg.kg-1 weight), and breast cancer with combination extract Dose 3 (P. urinaria 2000 mg.kg-1 weight + C. roseus 375 mg.kg-1 weight). Cheral was given orally for 14 days. The level of IL-17 was evaluated by flow cytometry analysis. The combination can suppress the expression of IL-17 which down regulation of IL-17 indicate a good prognosis for the breast cancer mice, for 6.17% in breast cancer condition to 0.93% with Dose 3 treatment. The combination can be used as immunomodulatory agent in humoral immunity through the regulation of IL-17. Keywords: Breast cancer, Catharanthus roseus, IL-17, Phyllanthus urinaria